Factors Associated with Utilization of Modern Family Planning Methods among Married Women of Tharu Community of Madhuwan Municipality in Bardiya District of Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: The use of modern family planning methods varies by province in Nepal from a low of 37% in Province 4 to a high of 49% in Province 3 There is no previous study has documented on the factors associated with utilization of modern family planning methods among married women of Tharu community in Bardiya district of Nepal, so this study is expected to provide information on influencing factors and hindering factors for utilization of family planning methods and its prevalence. MATERIALS AND METHODS: A Community based cross-sectional to find out factors associated with utilization of modern family planning method among married women of Tharu community of Madhuwan Municipality in Bardiya district of Nepal. Multistage cluster sampling was adopted. Sample size was calculated as 383. Face-to-face interview technique was adopted to collect data. Chi-square test was applied. A p-value of